Thermal conductivity of precursor derived Si–B–C–N ceramic foams using Metroxylon sagu as sacrificial template. Issue 1 (January 2015) - Kousaalya, Adhimoolam Bakthavachalam; Kumar, Ravi; Sridhar, B.T.N.
Abstract: Thermolysis of as-cast polyorganoborosilazane resulted in the formation of porous monolith of Si–B–C–N ceramic. However the addition of varying amounts of Metroxylon sagu (30–60 wt%) to polyorganoborosilazane, on thermolysis, resulted in Si–B–C–N foams. Thermo-gravimetric analysis of M. sagu revealed complete decomposition at 850 °C. Spark plasma sintering of Si–B–C–N was carried out at 1600 °C at a pressure of 30 MPa for 5 min in vacuum to obtain highly dense compacts. The obtained Si–B–C–N foam was found to be amorphous while the SPS-processed samples were observed to be highly crystalline. The geometrical density of the foam was found to vary from 0.4 to 0.25 g/cm 3 with increase in sago content along with the presence of both closed and open cells. The thermal conductivity of the foam and SPS-processed samples showed varying trends with increasing temperature due to the amorphous and crystalline nature of the samplesrespectively.